The Effect of Transactional Leadership on Employee Performance through Locus of Control as a Mediating Variable - Letwar, Erol Selvio; Risambessy, Agusthina; Rehatta, Pieter N. R. (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2025)
This study aims to analyze the influence of transactional leadership style on employee performance with locus of control as a mediating variable at PT. Telkom Akses Area Ambon. The population in this study consists of all leaders and employees of PT. Telkom Akses Area Ambon, totaling 158 people. The research sample consists of 60 respondents selected using a purposive sampling technique. Data processing was carried out using the Smart PLS 3 application, applying two analytical models: outer model and inner model. The results of the study show that transactional leadership has a positive and significant effect on employee performance. Transactional leadership significantly affects locus of control. Locus of control significantly influences employee performance. Locus of control serves as a partial mediator that helps strengthen the influence of transactional leadership on performance, although it does not fully mediate the relationship.